(untitled) (Journal of the College of Basic Education, 2022)
Any aesthetic idea, in order to achieve its presence, must have tools to establish a set of elements that establish the relationships of this internal and external idea as a discourse that has its message that arises from a preliminary idea of ​​development and is in the end a structure that has its significance that carries a meaning. Thus, the relations of ceramic art have multiple paths, including internal The compositional structure of ceramics, and the second is the relationships of these elements with space and through the visionary position of the recipient.